First genetic characterization of the brown dog tick Rhipicephalus sanguineus sensu lato in Peninsular Malaysia - Low, Van Lun; Prakash, Batah Kunalan (Springer, 2018)
The brown dog tick Rhipicephalus sanguineus sensu lato (s.l.) is a species complex comprising three main mitochondrial lineages, namely tropical, temperate and southeast European lineages. Despite its medical and veterinary importance, little attention has been paid to the genetic lineage of this species in Southeast Asia. Rhipicephalus sanguineus s.l. from Malaysia was investigated genetically, for the first time, using the mitochondria-encoded cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S) genes. Specifically, a pair of primers was developed to amplify the COI sequences in the present study. Both genes unambiguously assigned Malaysian material into the tropical lineage of R. sanguineus s.l. The 16S sequences were highly conserved; no variation site was observed. The COI sequences revealed slightly higher variation by recovering four haplotypes, one of which is restricted to the northernmost of Peninsular Malaysia. This finding will be a stepping stone in promoting more biological studies of this species complex in this region.